Financing Infrastructure and Monitoring Fiscal Risks at the Subnational Level - Liu, Lili (World Bank, Washington, DC, 2012)
This paper explores the building blocks of an institutional framework to govern borrowing by subnational entities to finance infrastructure investment. The framework should help in achieving sustainable financing of development needs and sound management of fiscal risks. Based on international experience, the authors suggest a minimum set of indicators for monitoring fiscal and debt developments. Recognizing the different nature and operations of the subnational entities, they propose specific indicators for special purpose vehicles and the government's general budget. The paper outlines an analytical framework to inform policy decisions concerning subnational debt limits, which are country-specific and should not be mechanically applied. Basic notions underpinning medium-term macro-fiscal frameworks and debt sustainability analyses provide effective guidance for identifying prudent levels of subnational debt. The authors argue that developing fiscal and debt indicators and setting borrowing limits should be part of a broader strategy to put in place an adequate fiscal architecture to coordinate and monitor the budgetary and borrowing policies conducted by individual subnational governments. Consistent with this general principle, they explore several areas of subnational public finance and management that need to be addressed with adequate governance structures and policy choices.